2002
DOI: 10.1539/joh.44.230
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electromagnetic Field on Free‐Radical Processes in Steelworkers. Part II: Magnetic Field Influence on Vitamin A, E and Selenium Concentrations in Plasma

Abstract: Effects of Electromagnetic Field on Free‐ Radical Processes in Steelworkers. Part II: Magnetic Field Influence on Vitamin A, E and Selenium Concentrations in Plasma: Andrzej Sobczak, et al. Department of General and Analytical Chemistry, Silesian School of Medicine, Poland—The aim of the study was the evaluation of the influence of electromagnetic fields (electric field strength of 20 V/m, f=50 Hz and magnetic field strength of 2 A/m, f=50 Hz) on the concentrations of vitamin A, vitamin E (a‐ and y‐tocopherol)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…This mechanism plays an important role when in the course of a chemical reaction the chemical bound is disrupted and two molecules with unpaired electrons are formed (a pair of radicals). Depending on their spin orientations, radical recombination or diffusion and formation of free radicals (e.g., Oxygen radicals) may take place Sobczak et al, 2002]. The radical pairs may be affected for a long and continuous time interval by the MF [Zmyslony et al, 2000].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This mechanism plays an important role when in the course of a chemical reaction the chemical bound is disrupted and two molecules with unpaired electrons are formed (a pair of radicals). Depending on their spin orientations, radical recombination or diffusion and formation of free radicals (e.g., Oxygen radicals) may take place Sobczak et al, 2002]. The radical pairs may be affected for a long and continuous time interval by the MF [Zmyslony et al, 2000].…”
Section: Discussionmentioning
confidence: 99%
“…There are reports about the short-term MF exposure that elicited an immune response [Repacholi and Greenebaum, 1999]. A potential link between MF and its effects on living organisms is the fact that MF causes an oxidative stress, that is, increase in the activity, concentration, and lifetime of free radicals [Scaiano et al, 1994;Li and Chow, 2001;Sobczak et al, 2002;Zhang et al, 2003]. Oxidative stress is a function of oxidative metabolites, free radicals, and reactive oxygen species (ROS) which are highly reactive byproducts of normal metabolism and immune defense [Dat et al, 2001].…”
Section: Introductionmentioning
confidence: 99%
“…However, it should be Fig. 1 Box plot shows distribution of TAS concentration in exposed group to ELF-MF and nonexposed group: Unexposed a KolmogorovSmirnov signiWcance: 0.028; Exposed b Kolmogorov-Smirnov signiWcance: 0.200 Table 4 Concentration of TAS, and GPX and SOD activities (mean § SAD) in exposed and nonexposed group The values given are mean § SD Independent samples test TAS total serum antioxidants, GPX glutathione peroxidases, SOD superoxide dismutase * P value = 0.065, ** P value = 0.003, *** P value = 0.001 noted that insigniWcance diVerence in TAS activity between two groups may be attributed to the short duration of exposure (median: 3 years) when compared to previous studies in which workers were exposed to ELF-MF for longer than 3 years Sohczak et al 2002). The mechanisms that explain this concurrent increase in TAS and decrease of the SOD and GPX activities are activationadaptation systems.…”
Section: Discussionmentioning
confidence: 90%
“…They also evaluated the erythrocytes' antioxidant status of steelworkers who were occupationally exposed to ELF-MF and found a signiWcant decrease of erythrocytes SOD and GPX activities, and an increased CAT activity in workers who were exposed to ELF-EMF for 3-10 years or longer. They have suggested that some adaptation-activation responses are involved in the body oxidative mechanism, balancing decrease in some antioxidants parameters and increase in others Sohczak et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism plays an important role when in the course of a chemical reaction, the chemical bond is disrupted, and two molecules with unpaired electrons are formed (a pair of radicals). Depending on their spin orientations, radical recombination or diffusion, and formation of free radicals (e.g., oxygen radicals) may take place Sobczak et al 2002). The radical pairs may be affected for a long and continuous time interval by the MF (Zmyslony et al 2000).…”
Section: Discussionmentioning
confidence: 99%